Bad debt: The women's mobilization against the financial industry in Kyrgyzstan. Issue 2 (July 2021) - Satybaldieva, Elmira
This article offers a first person account of women's mobilization against banking and microfinance sectors in Kyrgyzstan. It focuses on the key factors for the evolution of the anti-debt movement, and women's political strategies to problematize interest and to denaturalize the discourse of financial inclusion. For many years, the financial industry has operated a gendered process of neoliberal capital accumulation under the guise of empowerment that has produced tensions between transnational capital and marginalized women. Building upon Bourdieusian ideas on social movements, the study shows the significance of strain and situational definition in the formation of the anti-debt mobilization. The article uses in-depth interviews with the leaders and activists of the anti-debt movement and borrowers to explore how gender, class and capital were intertwined. It contributes to the literature on post-Soviet politics by challenging the dominant elite-centered frameworks, which are inadequate to explain local movements and gendered activism.